Nebulization by Isotonic Magnesium Sulphate Solution with Salbutamol Provide Early and Better Response as Compared to Conventional Approach (Salbutamol Plus Normal Saline) in Acute Exacerbation of Asthma in Children. - Akter, Tahmina; Islam, Md Nazrul; Hoque, Mohammad Azizul; Khanam, Suraya; Khan, Husnea Ara; Saha, Bijoy Kumar (Faridpur Medical College Journal, 2015)
Asthma attacks are serious respiratory problem that can be lethal when not treated appropriately. Till today the main stay of therapy is short acting ß2-agonist. Unfortunately in acute asthma episodes this is not enough to relieve the bronchospasm and reduce dyspnea. The shortcoming of ß2-agonist therapy has resulted in the use of a variety of other treatment in the management of acute asthma. The use of magnesium sulphate is one of the recent treatment options. This study was done to compare the efficacy of nebulized salbutamol with magnesium sulphate versus salbutamol with normal saline in the treatment of acute exacerbation of asthma in children. This randomized controlled trial was carried out among 60 patients with acute exacerbation of bronchial asthma fulfilling the inclusion criteria, admitted in the department of Paediatrics, Mymensingh Medical College Hospital over a period of one year from January 2009 to December 2009. They were distributed randomly, 30 patients received nebulized salbutamol (0.15mg/kg; minimum dose 2.5mg) with 2.0 ml of isotonic magnesium sulphate solution and another 30 patients received the same dose of salbutamol with 2.0 ml of normal saline on 3 occasions at 20 minute intervals. With single dose of nebulization in the magnesium sulphate with salbutamol group, by 20 minute almost all 26 (86.7%) patients achieved at least 60% of predicted PEFR. Within 20 minute from control group none could achieve 60% of predicted PEFR. After second dose of nebulization control group started achieving 60% of predicted value. Regarding response criteria, with second dose of nebulization, at 40 minute 16 (53.3%) patient from magnesium sulphate with salbutamol group showed good response (PEFR>70% predicted). But within the first 40 minutes, none could show good response in control group. With 3rd dose of nebulization all from magnesium sulphate group showed good response but even at 60 minute, 5 (16.7%) patients in control group failed to be included as good responder. In conclusion, nebulization by isotonic magnesium sulphate solution with salbutamol provide early and better response as compared to conventional approach (salbutamol plus normal saline) in acute exacerbation of asthma in children. Faridpur Med. Coll. J. 2014;9(2): 61-67